2020
DOI: 10.1002/eet.1905
|View full text |Cite
|
Sign up to set email alerts
|

The role of domestic policy coalitions in extractive industries' governance: Disentangling the politics of “responsible mining” in the Philippines

Abstract: Under what conditions do global regulatory norms become domesticated in highly contentious policy areas like oil, gas, and mining sectors? Departing from norm diffusion and environmental politics scholarship, the paper draws from the sociological literature on "coalition-building" to explain the partial, uneven adoption of global regulations aimed at setting standards for corporate behavior in the context of largescale mining. We process trace the variation in coalitional politics in the contemporary Philippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Such kinds of deliberation are expected to not only help countries in producing their EITI reports, but also in deciding on the EITI's scope, triggering public debates and considering broader reform processes (Yanuardi et al, 2021). Some research has shown that global norms such as the EITI affect countries' efforts to improve the quality of extractive industry governance in developing countries (Singh & Camba, 2020; Gustafsson et al, 2020; Macdonald & Nem Singh, 2020), including at the local level (Winanti & Hanif, 2020). Some countries, like Myanmar and the Philippines, even (voluntarily) initiated sub‐national MSGs, which shows that the EITI can become an arena to discuss social and environmental impacts of extractive industries (Vijge et al, 2019; EITI‐Philippines, 2020).…”
Section: Studying Social‐ecological Reflexivity In the Eitimentioning
confidence: 99%
“…Such kinds of deliberation are expected to not only help countries in producing their EITI reports, but also in deciding on the EITI's scope, triggering public debates and considering broader reform processes (Yanuardi et al, 2021). Some research has shown that global norms such as the EITI affect countries' efforts to improve the quality of extractive industry governance in developing countries (Singh & Camba, 2020; Gustafsson et al, 2020; Macdonald & Nem Singh, 2020), including at the local level (Winanti & Hanif, 2020). Some countries, like Myanmar and the Philippines, even (voluntarily) initiated sub‐national MSGs, which shows that the EITI can become an arena to discuss social and environmental impacts of extractive industries (Vijge et al, 2019; EITI‐Philippines, 2020).…”
Section: Studying Social‐ecological Reflexivity In the Eitimentioning
confidence: 99%
“…Data normalization was used to ensure rapid convergence and to acquire the lowest mean square error (MSE) values possible [45]. The normalized values of each input and output were achieved using Equation (1).…”
Section: Data Pre-processingmentioning
confidence: 99%
“…The Philippines is an archipelagic country consisting of more than 7600 islands in the Southeast Asian region. The Philippines is among the countries in the world with vast mineral deposits, and it was assessed that thirty percent of the land area of the country has the resources to commence mining activities [1]. Although the mining industry provides immense livelihood opportunities, mining activities in the Philippines have a mixed footprint of economic progress and impact on humans and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Those in power provide rhetorical support for environmental protections while at the same time fostering increased extraction. Activists expressed optimism that incoming president Rodrigo Duterte supported their actions, but his tenure has been marked by a continuation and escalation of extractivism (27,(42)(43)(44)(45).…”
Section: Governancementioning
confidence: 99%